The Study of Load Bearing Capacity of Bamboo Culm Bundles for The Design Applications in Small Public Building - Pongthana, Phattita; Rittironk, Supreedee (Journal of Architectural/Planning Research and Studies (JARS), 2015)
Bamboo is a natural material which is easy to find around the world. It is beautiful, strong, and suitable for using in construction. It can grow fast; it can be used as an alternative construction material that can become friendly to the environment. In bamboo construction, we know that bamboo has the limit of each culm to the loading carrying. Therefore, in order for the structure to carry more loads, quantity of bamboo culms should be increased. Most common method is to put culms together called “bundling”. There are also many techniques to do bundles. This research is aimed to study the loading capacity of bamboo culm bundles with various bundling methods in both column and beam application. The bundles of columns and beams are very straight forward method, so it is chosen to be investigated. The research also will provides the design guideline in choosing the right amount of culms and the right bundling method to design columns and beams. The research is the experimental research that does the finding by testing the loading capacity of setting specimens. The bamboo specie is selected to be Pai Sang Mon (Dendrocalamus Munro). The diameter is set to be the diameter of 8-10 centimeters. The variables in bundling methods are set to be 2 types. They are bamboo dowels with nylon rope and nuts and bolts. The amount of bamboo columns used in bundling in order to test the load carrying capacity is one to four culms. The method is to find load carrying capacity of bamboos by using ISO-22157 standards (Determination of physical and mechanical properties of bamboo). The load carrying capacity of bamboo columns and beams result appears to be highly increased if the amount of bamboo column increases. The load carrying from the bundling method with nuts and bolts appears to be higher than the bundling method with be bamboo dowels with nylon rope. The result of experimental research testing then are put to do modeling program, SAP2000 Educational Version. It is a tool to design and calculate the structural to finding sizing cross sectional, long culm and small public building.